Establishing a Multi-Country Sickle Cell Disease Registry in Africa: Ethical Considerations - Munung, Nchangwi Syntia; Nembaware, Victoria; de Vries, Jantina; Bukini, Daima; Tluway, Furahini; Treadwell, Marsha; Sangeda, Raphael Zozimus; Mazandu, Gaston; Jonas, Mario; Paintsil, Vivian; Nnodu, Obiageli E.; Balandya, Emmanuel; et al. (Frontiers in Genetics, 2019)
Abstract Sickle cell disease (SCD) is one of the most prevalent genetic conditions in sub-Saharan Africa. It is a chronic, lifelong disease often characterised by severe pain. However, SCD has received little investment in terms of health research, though there is currently a growing pool of SCD data from health and research facilities in different countries. To facilitate research on SCD in Africa, the SickleInAfrica consortium established a SickleInAfrica registry. The registry stores a systematic collection of longitudinal data from persons with SCD across sub-Saharan Africa, and currently, participants are being enrolled in Ghana, Nigeria and Tanzania. In establishing this registry, the SickleInAfrica consortium decided to actively identify and anticipate possible ethical issues that may arise in the development and management of the registry. This was motivated, in part, by the near absence of well documented ethical issues for registry research in Africa, more-so for registries enrolling participants across multiple countries and for a genetic condition. The consortium aims to establish standards for the equitable use of data stored in the registry. This paper presents a comprehensive report on the ethical considerations that came up in setting up a genetic disease registry across multiple African countries and how they were addressed by the SickleInAfrica consortium. Major issues included: active involvement of patients in the initiation and management of the registry; questions of assent and re-consent; the importance of ensuring that fears of exploitation are not replicated in African-African research collaborations; and the importance of public engagement in the management of registries. Drawing on this experience, SickleInAfrica plans to set up an ethics helpdesk for genetic disease registries and research in Africa.